The Nature of Intractable Conflict - Mitchell, C. author. aut Link
XI, 353 p.
Keywords: Building upon Mitchell's earlier work, The Structure of International Conflict, this volume surveys the field of conflict analysis and resolution in the twenty-first century, exploring the methods which people have sought to mitigate destructive processes including the creative and innovative new ways of resolving insoluble disputes.